Antibacterial Activity and Toxicity of Honey Derived from Bone, South Sulawesi, Indonesia - Zakaria, Zakaria; Misriyani, Misriyani; Astuti, Ayun Dwi; Masyita, Ayu (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Honey is a sweet substance produced by honey bees from the nectar of flowers or other parts of plants. Honey obtained from Bone, in South Sulawesi, has been extracted and tested for antibacterial activity and toxicity. Honey was macerated with methanol to obtain a crude extract. Methanol crude extract was then partitioned successively with n-hexane and ethyl acetate to obtain ethyl acetate and methanol fraction. Antibacterial activity test was performed by agar diffusion method against Escherichia coli and Staphylococcus aureus. Methanol extract, ethyl acetate fraction, and methanol fraction showed an inhibition zone against E. coli at 10.10, 10.05, and 8.40 mm, respectively with amoxicillin as a positive control (20.05 mm). Also against S. aureus, inhibition zone was obtained at 11.90, 9.30, 8.60, and 13.70 mm for methanol extract, ethyl acetate fraction, methanol fraction, and amoxicillin, respectively. The greatest inhibition zone was obtained from methanol extract against E. coli and S. aureus, both including the strong category. The LC50 value of methanol extract and methanol fraction was 273.57 µg/ml and 765.66 µg/ml, respectively, categorized as toxic against Artemia salina, while ethyl acetate fraction was not toxic.